Net electricity load profiles: Shape and variability considering customer-mix at transformers on the island of Oahu, Hawai'i. (December 2020) - Anukoolthamchote, Pam Chasuta; Assané, Djeto; Konan, Denise Eby
Abstract: This paper uses data provided by Hawaiian Electric Company (HECO) for the period from September 2010 to May 2014. The study explores the effect of customer mix of each distributed transformer on the shape of load profiles along with their variability. Results suggest that in a more residential-concentrated area, net load generally has two peaks — morning and night, while a more commercial-or industrial-concentrated area exhibits one midday peak. The shape of a given areas' load profile is mostly influenced by its customer-mix and the time-of-day, while its load volatility is largely the result of weather patterns and the level of PV penetration. Since solar power typically exhibits different generation characteristics from power produced by other conventional sources, more precise solar forecasts enable electric system operators to better manage electricity generation with fluctuating solar output. Highlights: Customer-mix at transformer level. Residential-concentrated area has peaks in mornings and nights. Commercial and industrial concentrated areas have peaks middays. Load profiles are influenced by customer mix and time of day. Load volatility is influenced by weather and PV penetration.